Спеціальні дослідження з виявлення акустоелектричних каналів витоку інформації - Павленко, Я. С. (ХНУРЕ, 2024)
Special studies on the detection of acoustoelectric channels of information leakage - this is a complex of measures aimed at detecting and blocking technical means that use acoustic waves for transmitting or intercepting information. Acoustoelectric transducers are devices that convert electrical signals into acoustic and vice versa, for example, microphones, speakers, sensors, etc. They can be used as embedded devices that create technical channels of information leakage, or as elements of electrical circuits that have side proper ties of acoustoelectric conversion. To detect acoustoelectric channels of information leakage, various methods and tools are used, such as scanning the radio frequency range, analyzing the radio electronic situation.
Keywords: акустоелектричний канал; канал витоку інформації